Molecular basis for clinical heterogeneity in inherited cardiomyopathies due to myopalladin mutations - Purevjav, Enkhsaikhan; Labeit, Siegfried (Human molecular genetics, 2012)
Abnormalities in Z-disc proteins cause hypertrophic (HCM), dilated (DCM) and/or restrictive cardiomyopathy (RCM), but disease-causing mechanisms are not fully understood. Myopalladin (MYPN) is a Z-disc protein expressed in striated muscle and functions as a structural, signaling and gene expression regulating molecule in response to muscle stress. MYPN was genetically screened in 900 patients with HCM, DCM and RCM, and disease-causing mechanisms were investigated using comparative immunohistochemical analysis of the patient myocardium and neonatal rat cardiomyocytes expressing mutant MYPN. Cardiac-restricted transgenic (Tg) mice were generated and protein–protein interactions were evaluated. Two nonsense and 13 missense MYPN variants were identified in subjects with DCM, HCM and RCM with the average cardiomyopathy prevalence of 1.66%. Functional studies were performed on two variants (Q529X and Y20C) associated with variable clinical phenotypes. Humans carrying the Y20C-MYPN variant developed HCM or DCM, whereas Q529X-MYPN was found in familial RCM. Disturbed myofibrillogenesis with disruption of α-actinin2, desmin and cardiac ankyrin repeat protein (CARP) was evident in rat cardiomyocytes expressing MYPNQ529X. Cardiac-restricted MYPNY20C Tg mice developed HCM and disrupted intercalated discs, with disturbed expression of desmin, desmoplakin, connexin43 and vinculin being evident. Failed nuclear translocation and reduced binding of Y20C-MYPN to CARP were demonstrated using in vitro and in vivo systems. MYPN mutations cause various forms of cardiomyopathy via different protein–protein interactions. Q529X-MYPN causes RCM via disturbed myofibrillogenesis, whereas Y20C-MYPN perturbs MYPN nuclear shuttling and leads to abnormal assembly of terminal Z-disc within the cardiac transitional junction and intercalated disc.
Gesehen am 27.11.2018